Cardiovascular health program with university students based on e-TEORISC: protocol for a clinical trial - João Cruz Neto; Tahissa Frota Cavalcante; Nuno Damácio de Carvalho Félix; Rafaella Pessoa Moreira (Revista Gaúcha de Enfermagem)
ABSTRACT Aim: To describe a study protocol to compare the difference between the risk of impaired cardiovascular function (00311) among university students as mediated by standard nursing consultation, when compared with nursing consultations mediated by the e-TEORISC. Method: Randomized, controlled and blinded clinical trial protocol. People with the NANDA-I nursing diagnosis of risk of impaired cardiovascular function (00311) will be included. Participants will be distributed, according to paired randomization by gender and number of etiological factors in nursing diagnosis 00311, into an intervention group (consultation and software based on the nursing theory studied) and a control group (standard nursing consultation). The main outcome will be the reduction of two or more etiological factors of the nursing diagnosis. The proposal was registered with the Brazilian Registry of Clinical Trials under number RBR-8y3qx39. Expected results: The implementation of the care program through e-TEORISC is expected to encourage the target audience to adhere to health services and allow care plans to be drawn up that reduce the etiological factors of the nursing diagnosis.